Violência contra os idosos na perspectiva dos profissionais do Programa de Saúde da Família em Uberlândia - MG - Vilela, Kenia Pereira (2009)
Elder abuse has received increasing attention in the field of health since it is a complex problem with consequences for the health of old people. It has been recognized as an important topic especially due to the aging of the world population, mainly in Brazil. This study aimed at assessing the knowledge of professionals from the Family Health Program (Programa de Saúde da Família, PSF) on elder abuse. Two hundred twenty-five professionals from the 34 PSF teams in Uberlandia were interviewed: 91 professionals with higher education degree (doctors, nurses, psychologists, dentists, social wokers, physiotherapists), 34 technical nurses and 100 out of the 202 existing community health agents who were selected randomly. Most of the professionals were female (193; 85.8%), young adults aged 18 to 29 years (88; 39.1%), mean age 34.6 years, median age 33 years. Fifty-eight percent of the community agents had completed high school, 17 (50%) of the technical nurses had completed their technical training and 57.1% of professionals with higher education degree had completed post-graduation. Most of the sample did not have specialization on family medicine (183; 81.3%): only 1 doctor (3.1%) and 15 nurses (44.1%) were family specialists. Among the 225 interviewed, 128 (56.9%) had more than 2 years of experience with PSF and 133 (59.1%) reported no previous information on elder abuse. Among those who had previous contact with the topic, 55 (59.8%) reported having heard of it from lectures. Seventy-eight professionals (34.7%) referred no previous knowledge on the Elderly Bylaw. Among those who reported at least some knowledge of it, 43 (29.3%) did not recall any of its content or articles and only 6 (4.1%) mentioned the need to report elderly mistreatment to official agencies. All the professionals of the sample were interested in getting information on elder abuse and 139 (61.8%) preferred doing so through workshops. This interest was justified by 188 (80.4%) of the interviewed due to the presence of the topic in their professional activities. One hundred twenty-two (54.2%) professionals reported previous suspicion of elder abuse. Among these, 85 (69.7%) referred to cases of neglect, 23 (18.9%) reported to official agencies, 9 of those (39.1%) were nurses. In a hypothetical situation, more than 70% of the professionals would recognize abuse but only a small percent would report it to official agencies. Although most of professionals (79.6%) have recognized the Elderly Council as the agency responsible for receiving reports on abuse, 81% did not know any information on its performance because they had never reported any case of elder abuse. Ninety-one (40.5%) professionals reported no reason for preventing them from reporting cases of elder abuse to official agencies. Among the remaining 134 professionals, 44 (32.8%) considered lack of information as a reason for preventing report. Almost all of the professionals (93.8%) identified the community agent as the responsible for screening situations of abuse and 44.2% identified them as also responsible for investigating these cases. Although most of professionals were able to recognize risk factors for elder mistreatment, many have also identified some protective factors as risk for abuse. Most of professionals referred making inquiries about care by family or caregiver, but 62.4% did these questionings in subtle ways. We conclude that there is lack of knowledge and inadequacy of clinical practice on elder abuse among professionals from PSF.